Vaccination of health professionals as a preventive measure against biological risk and disinformation - Tejada Pérez, Juan José; Vázquez-Vicente, Juan José; Martín-Martín, Francisco Gabriel; Herrera-Burgos, María Renée; Molina-Díaz, Joaquín Jesús; Lucerna-Méndez, María Ángeles (Revista Española de Comunicación en Salud, 2020)
Introduction: Vaccination is an essential tool in the prevention of highly contagious diseases. Currently, this procedure is becoming less widely used, due to various economic and social factors, among others, which have encouraged the reappearance of pathologies that were virtually disappeared. Objectives: To define the immune status of the health workers of the Hospital de Poniente and monitoring the effectiveness of vaccines administered by the Prevention Service on non-immunized health personnel. Methodology: A descriptive study evaluating by serology the immunity against measles, rubella, mumps, varicella and hepatitis B prior to and after the administration of vaccines to health personnel (n = 923). Results: A high percentage of the health worker population with protective antibodies against the microorganisms in the study was observed, either due to a correct vaccination schedule in childhood or due to subsequent vaccination by the Prevention Service (high rate of seroconversion). Conclusion: The study re-emphasizes the importance of vaccination as a preventive measure against the diseases analysed, justifying the need to launch information campaigns to strengthen their use.